A rare case of long-term joint swelling caused by pigmented villonodular synovitis in a 3-year-old girl: a case report - Liu, Yang; Liang, Shaohua; Wang, Wen (Frontiers in Surgery, 2023)
Clinical signs of pigmented villonodular synovitis (PVNS) are insidious and non-specific; therefore, delays in diagnosis and treatment are common. We describe a case of a 3-year-old patient presenting with long-term joint swelling to highlight the significance of considering PVNS as a differential diagnosis in children to prevent misdiagnosis and ensure early treatment. Traditional treatment of PVNS is open surgery and complete synovectomy. In this case, we were performed a minimally invasive knee arthroscopic excision. After the arthroscopic debridement, our patient has a favorable clinical outcome and without recurrence.